Diagnostics of Controlled Discrete-Nonlinear Dmitriev-Kislov System by Fractional Power Spectra - Afanasiev, V.V.; Loginov, S. S. (2021 Systems of Signals Generating and Processing in the Field of on Board Communications, 2021)
The features of diagnostics of a controlled multimode discrete-nonlinear Dmitriev-Kislov system based on the non-harmonic spectra of the generated signals are considered. Serial and parallel analyzers of fractional-power spectra based on selective suppression of signal components using fractional order differentiation and integration are proposed and compared. The multidimensional non-harmonic fractional-power spectra of signals of the discrete-nonlinear Dmitriev-Kislov system are investigated. An approach has been developed in the diagnostics of a controlled discrete-nonlinear system Dmitriev-Kislov, modified by control actions on the parameters of time sampling, based on fractional-power spectra of the generated 3-D signals.